2018
DOI: 10.1016/j.vibspec.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and simple chemical method for the preparation of Ag colloids for surface-enhanced Raman spectroscopy using the Ag mirror reaction

Abstract: Colloidal silver (Ag) nanoparticles (AgNP) have been widely used for surface-enhanced Raman spectroscopy (SERS) applications. We report a simple, rapid and effective method to prepare AgNP colloids for SERS using the classic organic chemistry Ag mirror reaction with Tollens’ reagent. The AgNP colloid prepared with this process was characterized using SEM, and the reaction conditions further optimized using SERS measurements. It was found that Ag mirror reaction conditions that included 20 mM AgNO3, 5 min react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Several research groups have used SMR to synthesize AgNPs. However, no study has described this novel phenomenon of AgNC formation and denucleation of SMR. Here, we first reported that SMR originally produced larger AgNCs, quickly denucleated, collapsed into small AgNPs, and then formed aggregates within a few minutes. It is unclear how SMR initially generates large AgNCs and why they rapidly collapse (or denucleate) into small AgNPs.…”
Section: Resultsmentioning
confidence: 94%
“…Several research groups have used SMR to synthesize AgNPs. However, no study has described this novel phenomenon of AgNC formation and denucleation of SMR. Here, we first reported that SMR originally produced larger AgNCs, quickly denucleated, collapsed into small AgNPs, and then formed aggregates within a few minutes. It is unclear how SMR initially generates large AgNCs and why they rapidly collapse (or denucleate) into small AgNPs.…”
Section: Resultsmentioning
confidence: 94%
“…Surface-enhanced Raman spectroscopy (SERS) is a novel analytical technique for trace contaminant determination which was realized by the enhanced local electromagnetic field near the nanostructured noble metal surfaces ( Bi et al., 2022 ; Panneerselvam et al., 2018 ). SERS technology can enhance the Raman signal intensity of target molecules by 10 4 –10 6 times ( Lam et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…4 SEM images of copper electrode surfaces before and after ORC different performances of SERS substrates, as the resonance of the laser with the surface plasmon requires a specific nanoparticle size for maximal enhancement. For chemical nanoparticle (NP) synthesis, the size distribution and, therefore, the Raman signal enhancement is easier to adjust and controllable by temperature and reaction time [59]. However, potentially utilized reducing agents and tensides may cause contamination of the Raman spectra with undesired remaining chemicals [53].…”
Section: Enhancement Methodsmentioning
confidence: 99%